Prospects for the use of wireless reading of prosthetic control signals and methods for generating commands. Issue 1 (January 2021) - Malakhov, D; Zhmud, V; Avrmachuk, V; Gryaznov, D; Nosek, J; Dimitrov, L
Abstract: The paper provides a rationale for the use of low-power wireless communication to create non-invasive bionic limb prostheses. The need for such a connection is dictated, on the one hand, by the expediency of using sensors located in various parts of the body, often very remote from each other, on the other hand, by the desire to free the disabled person's body from the wires that would envelop it like a spider web. For each of these positions, arguments are given.